Marketing Services: Competing Through Quality - Becker, Boris W.; Berry, Leonard L.; Parasuraman, A. (Journal of Marketing, 1992)
Excellent service is the foundation for services marketing, contend Leonard Berry and A. Parasuraman in this companion volume to Delivering Quality Service. Building on eight years of research, the authors develop a model for understanding the relationship between quality and marketing in services and offer dozens of practical insights into ways to improve services marketing. They argue that superior service cannot be manufactured in a factory, packaged, and delivered intact to customers. Though an innovative service concept may give a company an initial edge, superior quality is vital to sustaining success. Berry and Parasuraman show that inspired leadership, a customer-minded corporate culture, an excellent service-system design, and effective use of technology and information are crucial to superior service quality and services marketing. When a company's service is excellent, customers are more likely to perceive value in transactions, spread favorable word-of-mouth impressions, and respond positively to employee-cross-selling efforts. The authors point out that a service company that does relatively little pre-sales marketing but is truly dedicated to delivering excellent quality service will have greater marketing effectiveness, higher customer retention, and more sales to existing customers than a company that emphasizes pre-sale marketing but falls short during actual service delivery. The focus of any company, they insist, must be customer satisfaction through integration of service quality throughout the entire system. Filled with examples, stories, and insights from senior executives, Berry and Parasuraman's new framework for effective marketing servicescontains the key to high-performance services marketing.